(untitled) (International conference on multidisciplinary science, 2025)
Public debt management is a critical aspect of economic policy in developing countries, where fiscal challenges are often compounded by limited resources and external shocks. International financial institutions (IFIs) such as the International Monetary Fund (IMF) and the World Bank play a pivotal role in supporting these nations in managing their public debt effectively. This article examines the contributions of IFIs, including technical assistance, policy guidance, concessional financing, and debt restructuring initiatives. It highlights how IFIs help enhance debt sustainability, improve market access, and foster investor confidence. The article also addresses challenges such as conditionality, debt dependence, and the need for stronger local ownership of reforms. By drawing on examples from countries like Ghana, Jamaica, and Rwanda, it explores the successes and lessons learned from IFI-supported debt management programs. The article concludes with recommendations for maximizing IFI contributions through capacity building, transparency, and tailored strategies that align with the unique needs of developing economies.